The Effect of Cork Fish (Channa Striata) Extract on Perineum Wounds among Post-partum Clients - Rositah Rositah; Ita Herawati (STIKep PPNI Jawa Barat, 2022)
Aims: This study aimed to determine the effect of giving Cork fish extract (Channa Striata) on perineal wounds Methods: This quasi-experimental design research uses a one-group pretest-posttest design approach. Samples were collected using purposive sampling technique with total 40 post-partum mothers as respondents. Observation sheet used to measure perineal wound healing in the intervention and control groups Results: The average perineal wound healing between the intervention group (3.65) and control (5.50) in mothers in the Walantaka Public Health Center, Serang City. There was an effect of giving cork fish extract (Channa Striata) on perineal wounds with the result (p.value= 0.000). Conclusion: The result of this study showed that Cork fish extract can be used to perineal wounds among post-partum mothers. Further research about the other benefits and functions of Cork Fish Extract can be carried out, especially in the field of reproductive health.